Reflexiones de una docente: ser como un diapasón - Millán K., Teresa (Revista Hospital Clínico Universidad de Chile, 2014)
The following article compares what a universitary teacher in health sciences should be. The author stablishes an analogy with the tuning-fork, saying that the teacher should also try to evoke a harmonious response in terms of human relations.